Sustainable Empowerment as a Tool to Activate Brownfield - Mays K. Hamdan,; Shaimaa Hameed, (Iraqi Journal of Science, 2021)
The redevelopment of brownfields participate to sustainable urban development, it can make cities more valuable worth for community and more attractive for companies to settle down their projects through investment, and it can help to reduce expenditures for the construction of infrastructures and other services. Recent studies in brownfield redevelopment and investment have shown great interest in urban planning studies because of their negative effects on cities, they promoted sprawl, pollution, social and economic problems. There is a general agreement among researchers and experts that brownfield sites can be reused as green spaces, commerce centers, and residential projects. To promote sustainable urban development the role of the community must be strengthened and enabled to participate in the development process. The partnership between stakeholders such as community development organizations and investors are critical to promoting both communications and build confidence, which are important elements to a sustainable redevelopment program. The paper Highlights the role of community participation including society, public-private sector and local organization in activating brownfield projects through analysis several projects, from this analysis we point out that most of the brownfield project need huge corporation between community and public and private sector in addition to various disciplines such as urban planning, policy management and economic and environment aspect